2019
DOI: 10.3390/en12224231
|View full text |Cite
|
Sign up to set email alerts
|

Informed Citizen Panels on the Swiss Electricity Mix 2035: Longer-Term Evolution of Citizen Preferences and Affect in Two Cities

Abstract: For a successful transition to low-carbon electricity supply, public support is essential. Citizen preferences are best understood in the process of informed citizen panels, where citizens are informed about the pros and cons of various electricity technologies and spend time reflecting on the trade-offs. We investigated how information about electricity technologies and their sustainability impacts can change citizens’ preferences and affect for the complete Swiss electricity mix 2035. The citizens received i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…In order to form and elicit citizen preferences for the spatial siting of the full electricity mix in Switzerland, we adapted and merged two existing methodologies: informed citizen panels for the formation and elicitation of informed citizen preferences [42,44,45] and a serious board game with related evaluations before, during, and after the game [58,61,63,64]. The rationale here is that, in order to allow the citizens to make informed judgments that are close to their actual values, we, first of all, involve them in an informational process to fill their knowledge gaps, reduce misconceptions, and expose them to the judgments and perspectives of other citizens.…”
Section: Overall Process and Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to form and elicit citizen preferences for the spatial siting of the full electricity mix in Switzerland, we adapted and merged two existing methodologies: informed citizen panels for the formation and elicitation of informed citizen preferences [42,44,45] and a serious board game with related evaluations before, during, and after the game [58,61,63,64]. The rationale here is that, in order to allow the citizens to make informed judgments that are close to their actual values, we, first of all, involve them in an informational process to fill their knowledge gaps, reduce misconceptions, and expose them to the judgments and perspectives of other citizens.…”
Section: Overall Process and Measurementsmentioning
confidence: 99%
“…As shown in Figure 1, the workshop started with an explanation of its goals, content, and the rules of participation for participants' consent. Since previous research in Switzerland showed awareness gaps and misconceptions about electricity technologies [44,45,53], the participants were first introduced to short posters about each of the 11 technologies, including brief descriptions of how the technologies function, what their current situations are in Switzerland, as well as photos. The participants were also shown a short movie about the Swiss Energy Strategy 2050 [65].…”
Section: Overall Process and Measurementsmentioning
confidence: 99%
See 3 more Smart Citations